Legumes effect on nitrogen mineralization and microbial biomass potential in organic farming - Jalal, Arshad [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Oliveira, Carlos Eduardo da Silva [UNESP]; Khan, Ayesha; Boleta, Eduardo Henrique Marcandalli [UNESP]; da Silva, André Luis Máximo; Shah, Tariq (Elsevier, 2022)
Legumes in the organic farming system is an important alternative strategy to develop environmentally safe nitrogen (N) with low inputs and restore soil health in a suitable way for upcoming crops. The goal of this review was to evaluate environmental controls on legumes N fixation and soil N mineralization in the context of the diversified agroecosystem. To determine the prospective of legumes on N dynamics in soil, mainly soil N mineralization, soil microbial diversity, the interaction of legumes and soil microbes, soil enzymes, and their correlations for improving soil fertility and nutrient efficiency. Legumes-based organic farming strategies improved soil N mineralization and microbial diversity growth to alter soil quality (chemical attributes and enzymatic functions in relation to micro-biota) and biochemical responses to improve nutrients management in different climatic extremes. Legumes-based organic farming system also enhanced soil physics, chemistry, and biology and their linkage with soil biochemical reactions, N mineralization, soil microbial activities, and soil enzymes for subsequent crops. The current review also focused on the importance and principles of legumes in organic farming (theory and practices) to promote ecological friendly cultivation and production with an impact on soil health and their future perspective.
Keywords: Biological nitrogen fixation; Legumes-based cropping system; Nitrogen dynamics; Soil enzymes; Soil microbes; Soil quality